You never know which side you'll fall when you're sitting on the fence : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Stephens, Samantha Karin (Massey University, 2024)
This research examines the art of protest posters and what it means to engage in a public space as an artist. Primarily through text and printmaking, it explores what could start a dialogue around protest and current events in Aotearoa and globally. Graphic design, traditional, modern printmaking techniques such as urban street art, and both traditional and modern printmaking techniques have shaped this exegesis and creative body of work. The artists key to my practice are varied in media and influence; such as musicians Michael Franti, activists and multimedia artists The Guerrilla Girls, designers of The Wellington Media Collective and Barbara Kruger. This research project is concerned with discussion around issues facing Aotearoa and its current government’s policy and decision-making. Protest and protest art is core to how we discuss, react to, and unpack public issues. I am influenced by the process of making, creative practice research, design-art and modern protest material. The crux of this practice is making protest art publicly accessible to anyone.
Figures are reproduced with permission.
Keywords: 330316 Visual communication design (incl. graphic design); 360602 Fine arts